Shelf Sea Biogeochemistry: Nutrient and carbon cycling in a temperate shelf sea water column. (October 2019) - Sharples, Jonathan; Mayor, Daniel J.; Poulton, Alex J.; Rees, Andrew P.; Robinson, Carol
Abstract: This special issue presents some of the key findings from the pelagic component of the UK Shelf Sea Biogeochemistry Research Programme, carried out on the northwest European shelf between March 2014 and August 2015. The project aimed to address two issues: (1) how does a temperate shelf sea sustain an annual net drawdown and export of atmospheric CO2 without running out of inorganic nutrients, and (2) what uncertainties in processes or parameterisations within current ecosystem models can be reduced by a coordinated, multi-disciplinary observational programme covering the full seasonal cycle? Working with partners across Europe, the net annual drawdown of atmospheric CO2 over the entire northwest European shelf was confirmed. This demonstrated the context and impetus for a 17-month process study in the Celtic Sea, using a long-term mooring array and several research cruises, addressing shelf sea physics, inorganic and organic nutrient and carbon cycling, and bacterial, phytoplankton and zooplankton roles and dynamics. It was clear from the physics that all the carbon absorbed through the sea surface over one year was not exported to the open ocean. Physical transports were too weak and too slow to transport all the carbon-laden water over a wide shelf sea to the shelf edge within one year. The shelf sea must therefore be able to store carbon in a form that prevents release back to the atmosphere for a timescale that is sufficient to allow more episodic (timescales >1 year) exchange events to both remove the excess carbon and top-up the shelf pool of inorganic nutrients. The results presented in this special issue illustrate the likely key role of recalcitrant dissolved organic carbon in storing carbon on the shelf and highlight the need for longer-term measurements or monitoring to understand the nature and timing of potentially large but infrequent exchange events between the shelf and open ocean.